Altered Taste Perception for Sodium Chloride in Patients With Primary Aldosteronism: A Prospective Cohort Study - Adolf, Christian; Görge, Veronika; Heinrich, Daniel A.; Hoster, Eva; Schneider, Holger; Handgriff, Laura; Künzel, Heike; Sturm, Lisa; Beuschlein, Felix; Reincke, Martin (Hypertension (Dallas, Tex. 1979), 2021)
Rodents exposed to mineralocorticoid excess have considerably decreased taste sensitivity for sodium chloride (NaCl) and show high dietary sodium intake. A similar shift in NaCl taste perception could be detrimental in humans when aldosterone excess in primary aldosteronism (PA) causes hypertension and favors high sodium consumption. To investigate NaCl taste sensitivity in patients with PA, we studied NaCl taste recognition thresholds as measures of NaCl taste sensitivity in forty patients with PA before and after treatment of aldosterone excess. Forty patients with primary hypertension and 40 healthy normotensive volunteers served as controls. In this context, the subjects compared 10 different NaCl solutions (0.5–256 mmol/L) with distilled water. We also assessed individual NaCl intake using self-reported 24-hour recalls and duplicate determinations of sodium excretion in 24-hour urine. Patients with PA showed significantly higher NaCl taste recognition thresholds (median 32 versus 24 mmol/L in primary hypertension, P=0.010, and 16 mmol/l in normotensive control, P<0.001). Following specific treatment for PA, the taste recognition threshold for NaCl significantly improved in patients with unilateral PA undergoing adrenalectomy (median 16 versus 32 mmol/L at baseline, P=0.017) and in patients on MRA (mineralocorticoid receptor antagonists; median 16 versus 32 mmol/L at baseline, P<0.001) but was unaltered in healthy volunteers (median 16 versus 16 mmol/L at baseline, P=0.438). Our data show a significantly impaired NaCl taste perception in patients with PA. Surgical as well as medical treatment of PA significantly improved NaCl taste perception in patients with PA.